Entrepreneurship and Growth - An Overlapping Generations Approach - - Christiane Clemens (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2004)
This paper discusses a two–sector neoclassical overlapping generations economy with intermediate and final goods in the spirit of Romer (1990). The risk averse agents engage in one of two alternative occupations: either firm-ownership in the intermediate goods sector, characterized by monopolistic competition, or employment as a worker in this sector. The occupational choice under risk endogenizes the number of firms and products in the intermediate goods industry. Since entrepreneurial profits are stochastic, an inefficiently low number of agents chooses firm-ownership. We find that expected profits of monopolists do not vanish in equilibrium and that the level of economic performance is inefficiently low due to the presence of risk. This result carries over to a suboptimally low growth rate in an enodgenous growth context.
Keywords: D9; D4; D8; D5; O4; 330; OLG; occupational choice; monopolistic competition; growth